“Double band” technique for intractable or recurrent esophageal variceal hemorrhage: An alternative rescue method - Akar, Tarık (Turkish Journal of Gastroenterology, 2017)
Abstract Cite this article as: Akar T. “Double band” technique for intractable or recurrent esophageal variceal hemorrhage: an alternative rescue method. Turk J Gastroenterol 2017; 28: 535-6.